Got Milk? Using Nudges to Reduce Consumption of Added Sugar. Issue 1 (26th August 2019) - Lai, Chien‐Yu; List, John A; Samek, Anya
Abstract : The National School Lunch Program (NSLP) is a federal food assistance program that serves over 30 million children in the United States annually. Yet the impact of NSLP on nutritional intake may be limited because children frequently do not choose the healthier offerings or waste large portions of their meal. In this article, we study whether we can improve the impact of the NSLP on child food choice through low‐cost nudges. We conduct a field experiment in a school lunchroom with 2, 500 children, evaluating the impact of informational prompts on milk choice and consumption over two weeks. We find that prompts alone increase the proportion of children choosing and consuming the healthier white milk relative to sugar‐sweetened chocolate milk from 20% in the control group to 30% in the treatment groups. Adding health or taste messaging to the prompt does not seem to make a difference. We survey students and find that most prompts affect perceived healthfulness of the milk, but not perceived taste. Finally, we find that the prompts are nearly as effective as a small nonmonetary incentive.